Scalable and ligthway bio-inspired coordination protocol for FANET in precision agriculture applications. (March 2019) - De Rango, F.; Potrino, G.; Tropea, M.; Santamaria, A.F.; Fazio, P.
Abstract: The paper proposes a bio-inspired coordination protocol for Unmanned Aerial Vehicles (UAVs) management in the agriculture domain. In precision agriculture the presence of parasites or the sudden climatic changes represent an important issue for farmers because of the degradation of crops and cultivation quality. Then, the use of the new technologies such as UAVs devices, the new networks such as Flying Ad-Hoc NETwork (FANET), and the utilization of new sensors and actuators inside UAVs can represent an important aid to the smart agriculture domain. An important aspect is, surely, the adequate management and coordination of these new devices in order to plan specific strategies able to support adequately the agriculture humans' operators. Because drones are resource constrained and limited, scalable coordination techniques such those proposed can improve the network performance maintaining higher efficacy in the task execution.